Prevalence and risk factors of Helicobacter pylori infection in urban children aged 6–13 years in Fuzhou, China: a cross-sectional study in a high gastric cancer incidence region - Chen, Youtao; Pan, Xiaoting; Wang, Yanyan; Lin, Longzhen; Chen, Xiaoyan; Chen, Yan; Ye, Hong (Frontiers in Pediatrics, 2025)
BackgroundThe burden of Helicobacter pylori infection remains a global public health concern, particularly due to its lifelong risk of gastric cancer starting from childhood. Comprehensive data on the prevalence of H. pylori infection and associated risk factors among children are limited. This study aimed to investigate the prevalence and risk factors of H. pylori infection among children from Fuzhou, a high gastric cancer incidence region in southeastern China.MethodsIn this 2023 cross-sectional study, urban children aged 6–13 years were enrolled via stratified random sampling. Ethical approval was obtained prior to the study. Diagnosis was performed using the ¹³C-urea breath test, and risk factors were assessed through structured questionnaires covering demographics, lifestyle, diet, household conditions, and socioeconomic status.ResultsA total of 338 children were included. The overall prevalence of H. pylori infection was 22.2% (95% CI: 0.178–0.266), with age-specific rates increasing from 8.3% (6–7 years) to 34.7% (10–11 years). Multivariate logistic regression analysis identified frequent desserts/fried foods consumption as a risk factor (OR = 2.02, 95% CI: 1.13–3.63, p = 0.018), while higher annual household income was protective (OR = 0.567, 95% CI: 0.32–1.00, p = 0.048).ConclusionsThe age-dependent increase in H. pylori infection suggests cumulative environmental exposure. Modifiable risk factors (dietary habits, household crowding) and protective factors (income, hygiene practices) highlight the need for targeted public health interventions for pediatric populations at high risk.